Movement skills in the single art of pencak silat for students in martial art materials - Rozalini, Novia; Wulan Dari, Dewi Hijjah (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Learning self-defense pencak martial arts for physical education students is For understand essence about learning technique pencak silat and values art single in his learning . The most important part from learning self-defense pencak martial arts is prepare students to focus to assignment and practice material that has been prepared in teaching materials provided . Research purposes This is For know the skill level motion self-defense art single physical education student at Bina Bangsa University Gethsempena 2024. Type of research This is study Descriptive  Quantitative with using the test method Skills motion art single pencak martial arts . Retrieval technique sample that is with use technique total sampling ( Population Sample ) of 40 students . Deep data collection techniques study This using test instruments motion art single Pencak silat . Data analysis techniques using statistical calculations , namely counting average value and percentage . Research result This showing that : the "very good " category is 1 student with percentage of 2.5%, as many as 15 students is in the "Good" category with percentage 37.5%, 11 students are in the category “ Enough ” 27.5%, in the “Poor” category there were 8 students with percentage of 20% and 5 students in the "very poor " category with percentage 12.5%. So can is known that results evaluation Skills motion art single Physical Education student at Bina Bangsa University Gethsempena in 2024 it will be in the "Good" category with percentage 37.5%.